The effect of special exercises on selective attention for the performance of the "clinch" skill in wrestlers under 16 years of age - Shihap, Ammar; Shehab , Badraa; Atta, Shams (Journal of Physical Education, 2025)
Through the researcher's field follow-up and his knowledge of the wrestling game, he noticed that the level of performance of wrestling players is not at the required level. From the researcher's point of view, he sees that one of the reasons for this is due to their distraction as a result of the many variables present during the game. Therefore, the researcher decided to design special exercises in order to develop some mental aspects such as selective attention, which is the most important mental process and skill performance of the player. The aim of the research was to prepare special exercises and know their effect on selective attention and the performance of the lifting skill for wrestling players aged under (16) years. It was assumed that there were statistically significant differences between the experimental and control groups in the post-tests in both selective attention and the level of performance of the lifting skill. The researcher used the experimental method by designing two equivalent experimental and control groups with a pre- and post-test, on a sample of wrestling players under (16) years old, numbering (14) players. The variable of selective attention was tested And the skill of the porter in the wrestling game for the research sample after completing the main experiment and after processing the data statistically, the researcher concluded that the exercises prepared by the researcher proved effective in improving the level of selective attention and the skill of the porter in the wrestling game for the players.